The English Students' Critical Thinking Abilities with Learning Activities - Rei Christine Artauli; Sari Simbolon; Devi Agata Lubis; Rotua Theresia; Oriza Sativa Ellan (Universitas Lancang Kuning, 2024)
The goal of this correlation study is to examine how students' critical thinking relates to learning activities. This study investigates